Third IEEE and ACM International Symposium on Mixed and Augmented Reality
DOI: 10.1109/ismar.2004.59
|View full text |Cite
|
Sign up to set email alerts
|

The Effect that Haptically Perceiving a Projection Augmented Model has on the Perception of Size

Abstract: This paper reports on a study that investigated the effect touching a Projection Augmented model, and interacting with it using a spatially-coincident device, has on the perception of size. It was found that touching increased the accuracy of size estimates, however interaction using a spatially-coincident device did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Both a high level of object-presence and the ability to touch the PA model are important for many of these applications. Indeed, the size perception task in this experiment (not reported in this paper) found that touching a PA model increases how accurately a user perceives it [22]. However, these results suggest that touching this type of PA model reduces object-presence.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Both a high level of object-presence and the ability to touch the PA model are important for many of these applications. Indeed, the size perception task in this experiment (not reported in this paper) found that touching a PA model increases how accurately a user perceives it [22]. However, these results suggest that touching this type of PA model reduces object-presence.…”
Section: Discussionmentioning
confidence: 49%
“…They did this either by looking at it, or by both looking at and touching the PA model (Feedback IV). (The results of this specific task can be found in [22].) 4.…”
Section: Designmentioning
confidence: 99%
“…The tangible 3D tabletop developed by our research laboratory, CAVI [10], consists of a translucent table surface under which two cameras (1) and two projectors (2) are mounted (see Figure 2). Above the table, two additional projectors (3) are mounted.…”
Section: A Tangible 3d Tabletop Platformmentioning
confidence: 99%
“…Several researchers -Raskar et al [19], Bandyopadhyay et al [1], Raskar and Bimber [18], Bennett and Stevens [2,3] have explored technical challenges associated with the creation of realistic looking objects by projecting computergenerated images on neutral, three-dimensional physical objects.…”
Section: Introductionmentioning
confidence: 99%